Cover Picture: The Synthesis of Methylated, Phosphorylated, and Phosphonated 3′‐Aminoacyl‐tRNASec Mimics (Chem. Eur. J. 47/2013). Issue 47 (18th November 2013) - Rigger, Lukas; Schmidt, Rachel L.; Holman, Kaitlyn M.; Simonović, Miljan; Micura, Ronald
<x xml:space="preserve">Abstract</x> Selenocysteine is the only amino acid that is synthesized on its cognate transfer RNA, in all domains of life. Its biosynthesis involves the enzyme O‐phosphoseryl‐tRNA: selenocysteinyl‐tRNA synthase. To explore the enzyme mechanism, tRNASec substrates carrying aminoacyl moieties that mimic reaction intermediates are needed. The cover illustrates the synthetic path of phosphonated amino acid units to the 3′‐amide linked adenosine conjugates, subsequent assembly of RNA strands and enzymatic ligation to full‐length tRNASec derivatives. The cover also symbolizes the collaborative effort of the work from the two labs involved, R. Micura and co‐workers in Innsbruck (Austria) and M. Simonović and co‐workers in Chicago (USA). For more information see the Full Paper on page 15872 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>